A STUDY ON CONTENT-BASED INSTRUCTION (CBI) COURSE DESIGN FOR CHINESE AS A SECOND LANGUAGE: ——A CASE STUDY OF THE “5G MARKET” THEME SESSION - Huang, Xiao (泰国格乐大学 国际中文教学期刊, 2026)
This study explores the application of Content-Based Instruction (CBI) in teaching Chinese as a second language through the design and implementation of a three-hour thematic unit on the "5G Market" for intermediate-level learners. Following a content-driven approach, the course integrates adapted news discourse on 5G technology and its market implications, with activities sequenced as cognitive activation, linguistic scaffolding, deep processing, and integrated output. A Focus on Form strategy is employed to balance content depth with language accessibility. Data collected from ten learners’ anonymous written feedback were analyzed qualitatively. Results indicate that the course enhanced learner motivation, improved academic Chinese proficiency, increased language confidence, and deepened understanding of contemporary China. The findings support the effectiveness of CBI in fostering language-content integration. The study also discusses implementation challenges—particularly instructor expertise and material adaptation—and suggests future directions, including the development of diverse thematic units, shared teaching resources, and mixed-methods evaluations. Overall, this case offers a replicable framework for shifting CSL instruction from skill-based training toward the cultivation of subject-specific literacy and cross-cultural competence.